2018
DOI: 10.1148/radiol.2018171105
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Gadolinium in Human Cerebrospinal Fluid after Gadobutrol-enhanced MR Imaging: A Prospective Observational Cohort Study

Abstract: Purpose To determine whether gadolinium accumulates within cerebrospinal fluid (CSF) in patients recently exposed to the macrocyclic agent gadobutrol and identify factors that may affect this accumulation. Materials and Methods In this prospective observational cohort study, gadolinium was quantified by using inductively coupled plasma mass spectrometry of CSF samples from patients who underwent gadobutrol-enhanced magnetic resonance (MR) imaging followed by lumbar puncture within 30 days (gadobutrol group) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 18 publications
3
56
0
Order By: Relevance
“…Autopsy studies have shown that gadolinium deposition in the posterior fossa and basal ganglia is not limited to patients with intracranial abnormalities but can also be detected in patients with normal brains at the time of autopsy [17,18]. Several mechanisms of this gadolinium transit and retention in brain regions without impaired BBB have been suggested including active metal transporters [19,20], passage from the cerebrospinal fluid [21][22][23], and brain glymphatic system [24]. The exact mechanism behind the retention, however, remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies have shown that gadolinium deposition in the posterior fossa and basal ganglia is not limited to patients with intracranial abnormalities but can also be detected in patients with normal brains at the time of autopsy [17,18]. Several mechanisms of this gadolinium transit and retention in brain regions without impaired BBB have been suggested including active metal transporters [19,20], passage from the cerebrospinal fluid [21][22][23], and brain glymphatic system [24]. The exact mechanism behind the retention, however, remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…20 It has been further clarified that gadolinium contrast agents administered intravenously are distributed in cerebrospinal fluid in healthy subjects. 4,5,41 It has also been shown that gadolinium contrast agents in the cerebrospinal fluid spaces are transferred to brain parenchyma in animals and humans. 20,28,29,37,42 Thus, if gadolinium contrast is present in cerebrospinal fluid, it will also be present in brain parenchyma.…”
Section: Brain Parenchymamentioning
confidence: 99%
“…[25][26][27][28] This finding may be a part of the normal aging process; however, it also might be a biomarker of neurodegeneration. 15,26,28 To better understand the importance of GBCA leakage into the CSF from the cortical veins, we need more research. MRF can facilitate studies to further understand this phenomenon due to its brief scan time when we scan the limited number of slices of MRF.…”
Section: Mr Fingerprintingmentioning
confidence: 98%